2016
DOI: 10.4103/0971-9784.191576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiplatelet therapy on mortality and acute lung injury in critically ill patients: A systematic review and meta-analysis

Abstract: Aim:Platelet function is intricately linked to the pathophysiology of critical Illness, and some studies have shown that antiplatelet therapy (APT) may decrease mortality and incidence of acute respiratory distress syndrome (ARDS) in these patients. Our objective was to understand the efficacy of APT by conducting a meta-analysis.Materials and Methods:We conducted a meta-analysis using PubMed, Central, Embase, The Cochrane Central Register, the ClinicalTrials.gov Website, and Google Scholar. Studies were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…In observational studies, antiplatelet therapy was associated with a reduced incidence of ARDS but not of mortality. A previous meta-analysis conducted by Wang et al and Mohananey et al revealed decreased mortality among critically ill patients receiving antiplatelet therapy [ 25 , 40 ]. Notably, they included studies that did not report the incidence of ARDS [ 37 , 41 51 ] and possibly included patients at a lower risk of ARDS, which may confound the result [ 43 , 48 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In observational studies, antiplatelet therapy was associated with a reduced incidence of ARDS but not of mortality. A previous meta-analysis conducted by Wang et al and Mohananey et al revealed decreased mortality among critically ill patients receiving antiplatelet therapy [ 25 , 40 ]. Notably, they included studies that did not report the incidence of ARDS [ 37 , 41 51 ] and possibly included patients at a lower risk of ARDS, which may confound the result [ 43 , 48 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such patients include those who are unconscious, sedated, critically ill [ 24 ], elderly [ 25 ], or have dysphagia [ 26 ]. Moreover, all these scenarios are likely to be applicable to patients with cardiovascular disease [ 28 31 ] who may require antiplatelet therapy. Based on the current results, the ticagrelor OD tablet is considered a suitable alternative formulation to the 90-mg ticagrelor IR tablet for patients who are unable to swallow whole tablets, for whom there is a preference for an OD formulation, or for those who require nasogastric administration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dysphagia, a common problem in adults (~4% incidence in the USA [ 26 ]), may result in drug administration errors [ 27 ]. Such patients who are unable to take tablets encompass those with cardiovascular disease [ 28 31 ] who may need antiplatelet therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 47 ] Some studies suggest that antiplatelet therapy is associated with reduced mortality and lower incidence of ARDS/ALI. [ 48 49 ] Based on existing findings, antiplatelet agents may be effective in improving outcomes in patients with COVID-19.…”
Section: Hemostasis and Its Role In Management Of Covid-19mentioning
confidence: 99%